THE INFLUENCE OF SERVICE QUALITY AND HOSPITAL IMAGE ON THE LEVEL OF PATIENT SATISFACTION IN THE EMERGENCY INSTALLATION UNIT (IGD) HELSA JATIRAHAYU HOSPITAL IN 2024 - Aziz, Abdul; Ayu, Winda; Sanjaya, Titus; Dwinuarisha, Eggie (Jurnal Penelitian Kesmasy, 2024)
Introduction: When patients are dissatisfied with the health services they receive, they often choose to seek care at another hospital that offers better quality. Patient dissatisfaction can arise from various factors, including service quality and the hospital's reputation. Addressing these factors is essential for enhancing patient satisfaction. This research aims to assess how service quality and hospital image impact patient satisfaction in the Emergency Unit (IGD) of Helsa Jatirahayu Hospital in 2024. Research Method: The study employed a non-experimental, cross-sectional analytic design to eval__uate the influence of independent variables on the dependent variable. Data analysis was conducted using logistic regression software. The research involved a questionnaire distributed to Emergency Room patients at Helsa Jatirahayu Hospital. The target population consisted of 550 patients, from which a sample of 85 was selected. Data analysis was performed using SPSS Version 24.0. Results: The findings indicated that service quality significantly influenced patient satisfaction, with a p-value of 0.001 (p < 0.05) and an Odds Ratio (OR) of 5.161. This suggests that respondents who rated service quality poorly were 5.161 times more likely to be dissatisfied compared to those who rated it as good. Additionally, hospital image also affected patient satisfaction, with a p-value of 0.021 (p < 0.05) and an OR of 2.990, indicating that those perceiving a poor hospital image were 2.990 times more likely to report dissatisfaction than those who viewed the image positively. Overall, service quality and hospital image accounted for 75.8% of the variance in patient satisfaction, leaving 24.2% attributed to other unexamined factors.